Body Stalk Anomaly in a 9-Week Pregnancy - Fabio E. Quijano; María Mónica Rey; Mariana Echeverry; Roland Axt-Fliedner (Case Reports in Obstetrics and Gynecology)
Body stalk anomaly is a rare and severe malformation syndrome in which the exact pathophysiology and trigger factors are still unknown. This is a case of a 30-year-old patient who underwent ultrasound at 9 weeks of gestation. It revealed an abnormal location of the inferior body of the embryo in the coelomic space. The findings suggested a short umbilical cord syndrome. In order to confirm the diagnosis, the patient was scheduled for a second ultrasonography at 11 weeks of gestation. The obtained images, confirmed the location of the inferior body in the coelomic space with no visible bladder, absence of the right leg, severe abdominal wall defect, consistent with an omphalocele, and a short 5 mm umbilical cord. These last ultrasonographic findings were consistent with body stalk anomaly. Because of severe malformation incompatible with life, the patient was offered termination of pregnancy. Pathologic examination confirmed the suspected pathology of body stalk anomaly.